MORPHOLOGICAL CHARACTERISTICS OF RICE VARIETIES ON IRON STRESS IN NUTRIENT CULTURE MEDIA - Oktatora, Emilia; Agus Suwignyo, Rujito; Hasmeda, Mery; Damayanti, Rosa (BIOVALENTIA: Biological Research Journal, 2021)
Decreased rice productivity due to high iron concentrations especially in the vegetative phase, this causes the morphological character of rice to be affected until the metabolic process is disrupted. This study used 6 varieties, namely Batu Tegi, Inpara 9, Situ Patenggang, Inpara 8, Hawarabunar and Inpago 8, with iron concentrations of 0 and 250 ppm. The seeds were germinated for 3 days, then planted in Kimura B 10% nutrient culture media for 9 days, for 2 weeks then each week the media was changed to 100% Kimura B solution with the addition of 250 ppm iron concentration which was sampled every week until the 35th day. The results of the analysis of variance of the variables of plant height and root length showed that the combination Inpara 8-01 was the best combination and had a significant effect compared to other combinations with an average value of 61.31 cm and 30.77 cm. In the variable number of leaves the best average value was found in the combination of Batu Tegi-01 and Inpara 9-01 which had a significant effect compared to other treatments with an average value of 5.87 strands and 9.60 strands, respectively. On the stem dry weight variable, the combination of Hawarabunar-250 ppm Fe had a significant effect on other treatment combinations with the highest value of 0.17 g and the lowest value of treatment combination Inpara 9-250 ppm with a value of 0.08 g. Based on the results of treatment with 250 ppm Fe stress on plant morphological characters, the Hawarabunar variety had the best response in tolerating Fe stress, while the Batu Tegi variety was the lowest in tolerating Fe stress.